Tensor Analysis - Heinz Schade
Tensor calculus is a prerequisite for many tasks in physics and engineering. This book introduces the symbolic and the index notation side by side and offers easy access to techniques in the field by focusing on algorithms in index notation. It explains the required algebraic tools and contains numerous exercises with answers, making it suitable for self study for students and researchers in areas such as solid mechanics, fluid mechanics, and electrodynamics. Contents Algebraic Tools Tensor Analysis in Symbolic Notation and in Cartesian Coordinates Algebra of Second Order Tensors Tensor Analysis in Curvilinear Coordinates Representation of Tensor Functions Appendices: Solutions to the Problems; Cylindrical Coordinates and Spherical Coordinates.